2013
DOI: 10.1089/end.2013.0198
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cystatin C and NGAL as Early Biomarkers for Assessment of Renal Ischemia-Reperfusion Injury: A Serum Marker to Replace Creatinine?

Abstract: Cystatin C and NGAL both appear to be useful biomarkers of renal injury. Studies with larger numbers are needed, however. Also, allopurinol does exhibit renoprotective effects against ischemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…[16][17][18] Increased expression of these biomarkers was observed in our experiments, and KIM-1 was significantly elevated after IRI compared to off-clamp PN. This biomarker has been proven to be more sensitive than serum creatinine for AKI diagnosis and it may be a better method of evaluating renal function in the setting of IRI.…”
Section: Discussionsupporting
confidence: 70%
“…[16][17][18] Increased expression of these biomarkers was observed in our experiments, and KIM-1 was significantly elevated after IRI compared to off-clamp PN. This biomarker has been proven to be more sensitive than serum creatinine for AKI diagnosis and it may be a better method of evaluating renal function in the setting of IRI.…”
Section: Discussionsupporting
confidence: 70%
“…To date, there have been no objective clinical predictors for quantifying the degree of AKI and long-term renal function; until recently, NGAL has been reported as a useful marker for the early identification of ischemic and/or tubular damage [ 10 , 17 22 ]. However, not many human studies have documented the efficacy of NGAL in quantifying AKI following PN in patients with normal contralateral kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [32] found that RIPC produced by 3 cycles of intestinal brief ischemia protected against renal IRI in a rat model. Novel biomarkers (such as NGAL and cystatin C) have been proposed as early indicators of an upcoming renal failure [33]. NGAL is a protein belonging to the lipocalin superfamily initially found in activated neutrophils in accordance with its role as an innate antibacterial factor [34].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of diagnostic test studies, Haase et al [35] concluded that the NGAL level appears to be of diagnostic and prognostic value for acute kidney injury. Recently, Woodson et al [33] suggested that NGAL with cystatin C can be used as early biomarkers for the assessment of renal IRI in rats. In our model there is evidence that the RIPC II protocol has a better protective effect on IRI as NGAL serum levels were significantly lower than in RIPC I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation